The Role of the Driving Principal School And Teachers in the Independent Learning Program At Elementary School 003 Senaung Muaro Jambi Regency - Hermanto Hermanto; Mohamad Muspawi (Edumaspul: Jurnal Pendidikan, 2024)
The Independent Curriculum Program was formed to explore the potential of teachers in teaching and educating their students, as well as increasing student independence in learning. Teachers are the most important part in implementing independent learning. Teachers are also agents of educational transformation for the better. (Makarim, 2020). The aim of this research is to explain the role of school principals and teachers in the independent learning program. The method used in this research is the library method. The research results show that the principal and 5 roles of the teacher in the independent learning program are: 1) the teacher acts as a trainer for other fellow teachers, 2) the teacher plays the role of training student-centered learning, 3) the teacher acts as an agent of change, 4) The teacher's role is to create a learning space as a medium for discussion and collaboration, 5) The teacher's role is to guide the learning process, 6) The teacher's role is as a motivator, 7) The principal's role is to guide and ensure that the independent learning program is implemented according to applicable regulations.